Value engineering using Indonesia’s 2022 National Guideline through decision-making framework for cost optimization in highway infrastructure projects: a case study - Abma, Vendie; Citra Dwi Puspita Sari; Tri Nugroho Sulistyantoro; Rizki Budiman (Teknisia, 2026)
Infrastructure project often requires a balancing manage between design needs, functional performance, and limited financial resources. It has driven the need for Value Engineering (VE) methods to enhance projects and optimize cost without reducing the quality and performance. This study aims to explore the field implementation of Indonesia’s National Technical Guideline No. 4/P/BM/2022 by the Directorate General of Highways (Bina Marga) on VE within a toll road infrastructure project, using the Solo–Yogyakarta Toll Road (Package 1.2) as a case study. Emphasizing value optimization and cost optimization, the study adopts a mixed-method approach that integrates a Pareto principle-based identification of major cost components, a zero–one decision matrix to assess several common borrow material (CBM) sources, a cost–benefit evaluation, and expert insights from fifteen experienced highway engineers. The findings show that combining the use of both Wedi and Sampang quarries provides the best overall value, offering the optimal balance of haul distance, material quality, operational feasibility, and total project costs. The recommended choice results in a cost saving of IDR 51.16 billion (5.05%) while maintaining the required functional performance. Results of the study confirm that systematically implementing the national VE guideline can effectively guide decision-making, enhance project value, and deliver measurable economic benefits. The evaluative process developed offers a practical and replicable framework for applying VE procedures in infrastructure projects, especially in developing countries that need structured methods for cost optimization.